Evaluability assessment for Impact Evaluation: Guidance, checklists and decision support - and Peersman, Greet; Guijt, Irene; Pasanen, Tiina (ODI, 2015)
This guidance note focuses on the utility of, and guidance for, evaluability assessment before undertaking an impact evaluation. The primary audience for this guidance note is evaluators conducting an evaluability assessment for impact evaluation. The secondary audience is people commissioning or managing an evaluability assessment for impact evaluation, as well as funders of an impact evaluation. Sections one and two provide an overview of evaluability assessment and how it can be used for impact evaluation. Section three provides guidance for planning to undertake an evaluability assessment for impact evaluation. This is informative for all intended users of the guidance note. Section four includes checklists and decision support for evaluability assessments. The checklist is geared to those conducting the evaluability assessment and can be adapted to suit a particular context or purpose. The decision support provides those conducting an evaluability assessment with evidence-based recommendations for impact evaluation funders and commissioners, about whether, when and how to proceed with the evaluation. Sections five and six provide guidance on what to do after the assessment is concluded, and offer lessons learned from evaluability assessments in practice.